Exploring common bean fresh pod market in East African Region: A case of Uganda - Tamusange Nkalubo, Stanley; Ariong, Richard M.; Luyima, Gabriel; Mukankusi Mugisha, Clare; Rubyogo, Jean-Claude (MDPI, 2020)
Common bean fresh pod is a niche market product consumed worldwide including in Eastern Africa region. It is more preferred to dry bean due to the fresh taste and ease to cook. A lot of research has been done on production and disposition of dry bean product; however, little information is available on production and marketing of fresh bean pod in Uganda. The general observation indicates wide consumption of fresh bean pods however, there is limited information on its entire value chain, yet, its value cannot be undermined. Based on this background, a reconnaissance study was undertaken in Mpigi district, a major fresh bean growing area and eight retailing markets within Uganda’s capital, Kampala, to understand the economic feasibility of fresh bean pod market. Using qualitative approaches, farmer and market analysis was conducted to explore and understand fresh bean market dynamics. The results show that there are over 10 varieties being sold for fresh pod, unstandardized weight measures are being used, and price variation of over 50%. Additionally, unsatisfied demand for fresh pod beans is 45%. The results indicate existence of a lucrative fresh pod market valued at more than USD 2.0 million within Kampala and suburbs. It was also revealed that production faces significant gaps in seed availability to ensure consistent quality supply to the market while at selling points, bronzing effect was a major challenge leading to product deterioration. Thus, interventions are needed to eliminate the existing production and marketing challenges for a sustainable fresh bean pod business.